Photoprotection of Photosynthetic Pigments in Plant One-Helix Protein 1/2 Heterodimers - Psencik, Jakub; Hey, Daniel; Grimm, Bernhard; Lokstein, Heiko (The journal of physical chemistry letters, 2020)
One-helix proteins 1 and 2 (OHP1/2) are members of the family of light-harvesting-like proteins (LIL) in plants, and their potential function(s) have been initially analyzed only recently. OHP1 and OHP2 are structurally related to the transmembrane α-helices 1 and 3 of all members of the light-harvesting complex (LHC) superfamily. Arabidopsis thaliana OHPs form heterodimers which bind 6 chlorophylls (Chls) a and two carotenoids in vitro. Their function remains unclear, and therefore, a spectroscopic study with reconstituted OHP1/OHP2-complexes was performed. Steady-state spectroscopy did not indicate singlet excitation energy transfer between pigments. Thus, a light-harvesting function can be excluded. Possible pigment-storage and/or -delivery functions of OHPs require photoprotection of the bound Chls. Hence, Chl and carotenoid triplet formation and decays in reconstituted OHP1/2 dimers were measured using nanosecond transient absorption spectroscopy. Unlike in all other photosynthetic LHCs, unquenched Chl triplets were observed with unusually long lifetimes. Moreover, there were virtually no differences in both Chl and carotenoid triplet state lifetimes under either aerobic or anaerobic conditions. The results indicate that both Chls and carotenoids are shielded by the proteins from interactions with ambient oxygen and, thus, protected against formation of singlet oxygen. Only a minor portion of the Chl triplets was quenched by carotenoids. These results are in stark contrast to all previously observed photoprotective processes in LHC/LIL proteins and, thus, may constitute a novel mechanism of photoprotection in the plant photosynthetic apparatus.
Keywords: Photosynthesis; Chlorophyll; Carotenoids; proteiny vázající chlorofyl; Protein Multimerization; proteiny huseníčku; přenos energie; konformace proteinů; Light-Harvesting Protein Complexes; Protein Conformation; chlorofyl; Arabidopsis Proteins; karotenoidy; Energy Transfer; Chlorophyll Binding Proteins; Arabidopsis; Oxygen; kyslík; Kinetics; světlosběrné proteinové komplexy; Photochemical Processes; fotosyntéza; kinetika; multimerizace proteinu; fotochemické procesy